Mendelian Randomization Study on the Putative Causal Effects of Omega-3 Fatty Acids on Low Back Pain - Zhou, Shan; Zhu, Gaizhi; Xu, Yaqi; Gao, Ran; Li, Huan; Han, Gencheng; Su, Wenting; Wang, Renxi (Frontiers in Nutrition, 2022)
Previous observational studies have suggested an important role of omega-3 in lower back pain. In the present study, we used a two-sample Mendelian randomization (MR) study to identify the putative causal link between omega-3 and low back pain. A broadly used genome-wide association study (GWAS) (n = 8,866 individuals from European ancestry) were used to select plasma omega-3 genetic instrumental variables (IVs). A previously reported GWAS (4,863 cases and 74,589 controls from European ancestry) for low back pain were used to assess the effect of plasma omega-3 levels on low back pain. MR-egger_intercept and MR-PRESSO, and MR_egger and inverse variance weighted (IVW) in Cochran’s Q test were used to determine the pleiotropy and heterogeneity, respectively. MR-egger, weighted median, IVW, and weighted mode were used to perform MR analysis. Finally, the effect of a single SNP (single nucleotide polymorphism) was used to test the SNP bias. We did not find significant pleiotropy or heterogeneity of all six selected plasma omega-3 genetic IVs in low back pain GWAS. Expectedly, we found that as plasma omega-3 levels genetically increased, the risk of low back pain had a decreased trend using MR-egger (Beta = -0.593, p = 0.228; OR = 0.553) and weighted mode (Beta = -0.251, p = 0.281; OR = 0.778). This reduced trend was further proven by weighted median (Beta = -0.436, p = 0.025; OR = 0.646) and IVW (Beta = -0.366, p = 0.049; OR = 0.694). Our analysis suggested a putative causal link between genetically increased plasma omega-3 levels and the reduced risk of low back pain in European ancestries. Thus, the supplementation of omega-3 may be important for the prevention and treatment of low back pain.